PENERAPAN METODE MATERIAL REQUIREMENT PLANNING (MRP)DALAM PERENCANAAN KEBUTUHAN BAHAN BAKU KEMASAN PLASTIK HD MAYOR - Taufiq Sanjaya; Djoko Adi Waluyo (WAKTU, 2013)
The raw material is a major component in an industry, where raw materials become afundamental requirement in the production process. That requires a careful inventory planningsystem in the processing of raw materials production. If adequate supplies of raw materials, theproduction continues to run smoothly. Material Requirement Planning (MRP) is a method forcontrolling the raw material inventory planning. Where this method is designed specifically forthe production of corrugated demand situation. With this method, the researchers conducted astudy of HD plastic packaging raw material inventories at a food company, in which the process ofcollecting data with historical data recording system usage reports monthly HD plastic.The purpose of this study was to determine inventory levels and determine strategies forcontrolling and planning of HD plastic packaging materials. By making MPS for 3 months, thenthe obtained forecasting production from December 2012 s/d in February 2013. The doughproduction amount of demand Adonan 32.543batch and demand of Cream 95.938batch.With the number of such requests, the need for plastic packaging materials as much HD plasticshort 24zak as same 7221.45Kg, equivalent to as much as 604.79Kg weekly demand. For HDplastic long needs 19zak as same 5610.86kg, equivalent to 467.57Kg weekly demand. By usingthe MRP method can determine the company's raw material procurement strategy for the next 3months. Thus the MRP method can be applied in the raw material requirement planning.